„Nehmt auf euch mein Joch und lernt von mir!“ (Mt 11,29): Mt 11,28–30 und die christologische Dimension der matthäischen Ethik - Konradt, Matthias (Zeitschrift für die neutestamentliche Wissenschaft, 2018)
An analysis of the Christological dimension of Matthean ethics that discusses onlyJesus’ attitude towards the Torah, which has taken centre stage in recent Matthean research, is insufficient, as Jesus’s ethical instruction does not consist only in Torah-related teaching. Moreover, Jesus himself functions as a paradigm for his disciples’ conduct. In this connection, Matt 11,28–30 bears paradigmatic significance. This text presents Jesus not as personified Wisdom, but as the humble messianic king who invites the people to take shelter under his gentle rule. Alongside Jesus’ instruction itself, the admonition to learn from him also includes the mimetic aspect of following his example. Furthermore, an adequate analysis of Matthean ethics must take into account that the development of ethically relevant elements is interwoven in the narrative development of the Jesus story and correlated with the thematic shifts in that narrative. Matt 11,28–30 is an important building block in the macrostructure of this narrative dynamic.